Tourism and Authenticity in the Czech Villages of the Romanian Banat - Hoření, Karina; Krylová, Radoslava; Ulčák, Zbyněk; Klvač , Pavel (Journal for Geography, 2010)
In the 1820s, several thousand Czechs moved to the Carpathian Mountains region near the Danube river. They founded six villages. Strict ethnic endogamy helped preserve their cultural distinction. Nowadays these villages are visited by tourists from the Czech Republic. Visits are motivated by the search for both “traditional” rural landscape and lifestyle. The paper analyses the ways of how tourists perceive the rural landscape and lifestyle, how their perceptions vary and how they influence their behaviour. It is assumed that there is a sentiment for traditional, pre-modern world. This sentiment is used for tourism promotion there. Therefore the “harmonic cultural landscape” does not only have ecological and cultural value, but its image becomes a commodity in the tourism industry.
Keywords: tourism; authenticity; Banat; myth; landscape character